Human Error, Safety and Systems Development 7th IFIP WG 13.5 Working Conference, HESSD 2009, Brussels, Belgium, September 23-25, 2009, Revised Selected Papers - Palanque, Philippe; Vanderdonckt, Jean.; Winckler, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 7th IFIP WG 13.5 Working Conference on Human Error, Safety and Systems Development, HESSD 2009, held in Brussels, Belgium, in September 2009. The 8 revised full papers presented with were carefully reviewed and selected from numerous submissions for inclusion in the book. The papers address the problem of developing systems that support human interaction with complex, safety-critical appications. The papers are organized in topical sections on human factors in healthcare systems, pilot's behaviour, ergonomics and safety critical sysems.
Invited Talk -- New Requirements for Modelling How Humans Succeed and Fail in Complex Traffic Scenarios -- Human Factors in Healthcare Systems -- Integrating Collective Work Aspects in the Design Process: An Analysis Case Study of the Robotic Surgery Using Communication as a Sign of Fundamental Change -- Patient Reactions to Staff Apology after Adverse Event and Changes of Their Views in Four Year Interval -- A Cross-National Study on Healthcare Safety Climate and Staff Attitudes to Disclosing Adverse Events between China and Japan -- Pilot$1 (Bs Behaviour -- Cognitive Modelling of Pilot Errors and Error Recovery in Flight Management Tasks -- The Perseveration Syndrome in the Pilot$1 (Bs Activity: Guidelines and Cognitive Countermeasures -- Ergonomics and Safety Critical Systems -- First Experimentation of the ErgoPNets Method Using Dynamic Modeling to Communicate Usability Evaluation Results -- Contextual Inquiry in Signal Boxes of a Railway Organization -- Reducing Error in Safety Critical Health Care Delivery.s
Keywords: Computer science; Information systems; Multimedia systems; Astronautics; System safety; Computer Science; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Aerospace Technology and Astronautics; Quality Control, Reliability, Safety and Risk; Information Systems and Communication Service; Media Design